1982
DOI: 10.1083/jcb.95.1.355
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of von Willebrand protein in Weibel-Palade bodies of human endothelial cells

Abstract: Immunofluorescence staining of cultured human umbilical vein endothelial cells has shown the presence of von Willebrand protein in the perinuclear region, in small rodlike structures through the cytoplasm, and on filaments of the extracellular matrix. Nonendothelial cells showed no staining with anti-von Willebrand protein antiserum. At the light microscope level, immunoperoxidase treatment of endothelial cells revealed the same pattern and antibody specificity as the fluorescence staining. Thin sections of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
345
0
9

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 646 publications
(362 citation statements)
references
References 26 publications
(19 reference statements)
8
345
0
9
Order By: Relevance
“…The soluble protein content of a-granules was shown to be synthesized normally but improperly packaged and lost in the demarcation membrane system early during megakaryocyte maturation (4,28). We describe the presence oftypical WPB, the specific storage organelles for vWF ( 16), in endothelial cells from two patients with GPS with normal ultrastructure and normal internal distribution of both vWF and P-selectin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soluble protein content of a-granules was shown to be synthesized normally but improperly packaged and lost in the demarcation membrane system early during megakaryocyte maturation (4,28). We describe the presence oftypical WPB, the specific storage organelles for vWF ( 16), in endothelial cells from two patients with GPS with normal ultrastructure and normal internal distribution of both vWF and P-selectin.…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells, the vWF is stored in Weibel-Palade bodies (WPB), in its highest molecular weight form (16)(17)(18)(19), whereas in megakaryocytes and platelets, vWF is localized in a-granules, along with many other hemostatic proteins (20,21). Both WPB and a-granules are lined by a single membrane that contains P-selectin (8,22,23), a glycoprotein involved in monocyte and neutrophil recognition (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…14,[26][27][28] Control experiments indicated that Fg added to breast cancer or endothelial cells was not processed further by protease degradation or crosslinking to higher ordered structures (data not shown). Synthetic peptides corresponding to the Fg b-chain primary structure were custom synthesized as previously described, 11 and include b , b [15][16][17][18][19][20][21][22][23][24][25][26][27] , b 18-31 and b [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] (Table I). Fibrinopeptide A (Bachem) was used as a nonspecific peptide for permeability studies.…”
Section: Fibrinogen Purification and Synthetic Peptidesmentioning
confidence: 99%
“…24 EC used for permeability and TEM assays were cultured in phenol red-free McCoy's 5A with 5% fetal bovine serum without ECGS and heparin. The HMEC-1 human dermal microvascular endothelial cell line was cultured in MCDB-131 (Invitrogen) with 10% fetal bovine serum, 10 ng/ml recombinant human EGF and 1 lg/ml hydrocortisone (Sigma).…”
Section: Cell Culturementioning
confidence: 99%
“…Studies in vitro have suggested that this stabilizing effect is enhanced when F.VIII and vWF are co-expressed in the same cell, rather than simply adding vWF to the media (219,228). However, while vWF is believed to be produced in endothelial cells, platelets, and megakaryocytes, the site of F.VIII synthesis is somewhat controversial (229)(230)(231). The liver has been implicated as a major site of F.VIII synthesis due to the ability of liver transplantation to cure hemophilia A in canine models as well as human patients (232)(233)(234).…”
Section: Additional Challenges In Hemophilia Amentioning
confidence: 99%